The Quest for Rare Variants: Pooled Multiplexed Next Generation Sequencing in Plants - Marroni, Fabio; Pinosio, Sara; Morgante, Michele (Frontiers in Plant Science, 2012)
Next generation sequencing (NGS) instruments produce an unprecedented amount of sequence data at contained costs. This gives researchers the possibility of designing studies with adequate power to identify rare variants at a fraction of the economic and labor resources required by individual Sanger sequencing. As of today, only three research groups working in plant sciences have exploited this potentiality. They showed that pooled NGS can provide results in excellent agreement with those obtained by individual Sanger sequencing. Aim of this review is to convey to the reader the general ideas underlying the use of pooled NGS for the identification of rare variants. To facilitate a thorough understanding of the possibilities of the method we will explain in detail the variations in study design and discuss their advantages and disadvantages. We will show that information on allele frequency obtained by pooled next generation sequencing can be used to accurately compute basic population genetics indexes such as allele frequency, nucleotide diversity and Tajima’s D. Finally we will discuss applications and future perspectives of the multiplexed NGS approach.